(untitled) (Jurnal Simki Economic, 2023)
The purpose of this research is to determine the influence of social media marketing, brand image, and lifestyle on the purchase decision of Starbucks products in the Jabodetabek area. The methodology employed in this study is a quantitative approach aimed at testing predetermined hypotheses. The population of this research consists of Starbucks customers in the Jabodetabek area. The sample size for this study is 135 respondents. Multiple linear regression analysis is used as the analytical tool in this research. The findings of this study indicate that social media marketing and brand image have a significant influence on purchase decisions, while lifestyle does not affect on purchase decisions. The limitations of this research include the scope of the research objects. The results of this study can be utilized as literature review for various stakeholders within the company to improve management and operational aspects of the business, as well as to serve as a basis for company policy-making in enhancing purchase decisions among customers.